Answer: Choice B
![x^2+y^2 = (1)/(2)(x+y)^2 + (1)/(2)(x-y)^2](https://img.qammunity.org/2023/formulas/mathematics/college/qutzpivbxsytqbvtbi1j1vgl6aoalrlzoe.png)
===================================================
Step-by-step explanation:
Let's go through the answer choices to see which are true and which are false.
------------------------
Choice A is false because it should be
![x^2-y^2 = (x+y)(x-y)](https://img.qammunity.org/2023/formulas/mathematics/college/86fyvvl08e1udme3sctimhi77wh13g2pff.png)
which is the difference of squares factoring rule.
However, the left hand side of choice A has a plus, and not a minus.
Consequently, this rules out choice D.
------------------------
Choice B is true
We can conclude this by eliminating the other answer choices as false, and by noticing the following:
![x^2+y^2 = (1)/(2)(x+y)^2 + (1)/(2)(x-y)^2\\\\x^2+y^2 = (1)/(2)(x^2+2xy+y^2)+(1)/(2)(x^2-2xy+y^2)\\\\x^2+y^2 = (1)/(2)x^2+xy+(1)/(2)y^2+(1)/(2)x^2-xy+(1)/(2)y^2\\\\x^2+y^2 = x^2+y^2](https://img.qammunity.org/2023/formulas/mathematics/college/zqt2q7kikrk705yx8czzsy6gbgdy1ou53f.png)
This confirms why choice B is an identity. The equation is true for any real numbers x and y.
Let's look at an example. I'll pick x = 4 and y = 7
![x^2+y^2 = (1)/(2)(x+y)^2 + (1)/(2)(x-y)^2\\\\4^2+7^2 = (1)/(2)(4+7)^2 + (1)/(2)(4-7)^2\\\\16+49 = (1)/(2)(11)^2 + (1)/(2)(-3)^2\\\\65 = (1)/(2)(121) + (1)/(2)(9)\\\\65 = 60.5+4.5\\\\65 = 65\\\\](https://img.qammunity.org/2023/formulas/mathematics/college/mt6sbycggur83fxg1rabsf1tsamzory7t3.png)
I'll let you try other (x,y) pairs of values. Keep in mind that using numeric examples like this is not a proof. The proof would be using algebra to expand and simplify the right hand side so it becomes the left hand side.
------------------------
Choice C is false. The right hand side
expands out to
![x^2+2xy+y^2](https://img.qammunity.org/2023/formulas/mathematics/college/veq2r3nfkkvnuf8rj0czirp4nj9v6wmpx0.png)
A common mistake students do is to forget about the 2xy when expanding out
, which may lead to choice C being a slight trick answer.
If choice C said
, then we'd have a true identity
------------------------
Choice D is false. Refer to the formula I wrote in choice A.